1989
DOI: 10.1007/bf00932321
|View full text |Cite
|
Sign up to set email alerts
|

Flucloxacillin compared with cefazolin in short-term prophylaxis for clean orthopedic surgery

Abstract: Two-hundred and fifty-two patients were included in a prospective, randomized, double-blind trial comparing the efficacy of flucloxacillin with that of cefazolin for clean orthopedic surgery. The preventive antibiotic regimen consisted of three 1-g injections perioperatively. There were 126 patients in each group, and the follow-up period was at least 6 months. Two deep (1.6%) and five superficial (4.0%) infections occurred in the flucloxacillin group. Three deep (2.4%) and five superficial (4.0%) infections d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…We found no significant effect of antibiotic prophylaxis in hip fracture patients and we are in agreement with several randomized [3,7,9,10,11] studies. It is doubtful whether antibiotic prophylaxis should be given to hip fracture patients.…”
Section: Discussionsupporting
confidence: 92%
“…We found no significant effect of antibiotic prophylaxis in hip fracture patients and we are in agreement with several randomized [3,7,9,10,11] studies. It is doubtful whether antibiotic prophylaxis should be given to hip fracture patients.…”
Section: Discussionsupporting
confidence: 92%
“…(1,2). Cephalosporins and other antibiotics are used widely for prophylaxis, and several reports have compared other antibiotics with cephalosporins (3,4). The…”
Section: Introductionmentioning
confidence: 99%
“…Further hand searching of a Cochrane Review [28] (found through the electronic search) identified an additional study [29]. Hand searching of journals for RCTs also identified three articles [3032].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty one studies were excluded as they were randomized trials performed on primary THA and TKA only [22, 25, 26, 27, 31, 4367]. Nine studies were excluded due to the fact that the number of revision THA/TKA procedures and corresponding infections could not be broken out from primary THA/TKA [29, 68–75]. Three studies were excluded as they were for revisions of infected primary THA/TKA and the antibiotics administered were for treatment and not for prophylaxis [7678].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation